2020
DOI: 10.1007/s13273-020-00104-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma α-synuclein in idiopathic Parkinson’s disease patients after adjusting hemolysis factor

Abstract: Background Lewy bodies are pathological hallmarks for the diagnosis of Parkinson's disease, where the core components are composed of aggregated forms of α-synuclein (α-syn). Although α-syn has been investigated as a potential biomarker for PD, its usage has been limited and still remains controversial. Objective An accurate enzyme-linked immunosorbent assay (ELISA) was developed for the detection of α-syn in plasma. The hemolysis score was calculated to eliminate the additive α-syn levels from RBCs. Human pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…As lumbar puncture is an invasive procedure, differences in α-syn levels have been explored in more accessible biofluids, like blood. In this regard, several studies have showed contradictory results, some authors finding increased levels of plasma or serum α-syn in PD patients [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], whereas others found no changes [22][23][24][25][26][27][28][29][30][31][32][33][34][35] or even reduced levels [36,37]. The analysis of different proteoforms of α-syn, like oligomeric (o-syn) and phosphorylated (p-syn) forms, has raised equally variable results [13,22,26,28,32,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…As lumbar puncture is an invasive procedure, differences in α-syn levels have been explored in more accessible biofluids, like blood. In this regard, several studies have showed contradictory results, some authors finding increased levels of plasma or serum α-syn in PD patients [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], whereas others found no changes [22][23][24][25][26][27][28][29][30][31][32][33][34][35] or even reduced levels [36,37]. The analysis of different proteoforms of α-syn, like oligomeric (o-syn) and phosphorylated (p-syn) forms, has raised equally variable results [13,22,26,28,32,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, α-syn has been studied extensively as a potential biomarker and indicator of disease progression in PD and its related synucleinopathies (El-Agnaf et al, 2003;Hong et al, 2010;Devic et al, 2011;Mollenhauer et al, 2011;Shi et al, 2011). However, inconsistent plasma α-syn data in PD have been reported, and the diagnostic performance of α-syn in biofluids was still insufficient for application in PD diagnosis (Lee et al, 2006;Li et al, 2007;Foulds et al, 2011Foulds et al, , 2013Gorostidi et al, 2012;Ishii et al, 2015;Lin et al, 2017;Shim et al, 2020). The absence of reliable biofluidic biomarkers for PD has limited the monitoring of disease progression or treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies addressing serum and/or plasma aSyn levels in PD patients compared with controls are summarized in Table 1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 5...…”
Section: Studies Addressing Serum/plasma Asyn Levelsmentioning
confidence: 99%